Perforated two-dimensional nanoarchitectures for next-generation batteries: Recent advances and extensible perspectives. (February 2021) - Nazarian-Samani, Masoud; Haghighat-Shishavan, Safa; Nazarian-Samani, Mahboobeh; Kashani-Bozorg, Seyed Farshid; Ramakrishna, Seeram; Kim, Kwang-Bum
Abstract: In the past decade, nanoperforated graphene (also known as a graphene nanomesh or holey graphene) has attracted considerable research interest worldwide, predominantly because of its superior properties such as superb electronic properties with a tunable band gap, greatly enhanced mass and charge transport, high specific surface area with abundant useful reaction/adsorption sites and functionalities, and excellent magnetic, photocatalytic, and mechanical properties. Considering the most recent research activities, this comprehensive review first concentrates on the characterization and synthesis particulars of chemistry-based strategies for several state-of-the-art 2D holey nanoarchitectures, including holey graphene, nitrogenated holey carbon networks (C2 N), holey graphitic carbon nitride (g-C3 N4 ), and carbon nanomeshes, as well as 2D holey metal oxides, nitrides, sulfides, phosphides, hydroxides, selenides, carbides, carbonates, oxyfluorides, and NASICON-type structures. The pros and cons of each method for designing in-plane nanoperforations are also highlighted. Subsequently, we discuss the electrochemical properties for next-generation batteries including Li–O2, Zn–air, Li–CO2, Li–S, Li–Se, Li–Sex Sy, and K-ion batteries, while comprehensively evaluating all the parameters that help in improving their performance owing to the existence of the introduced in-plane holes. Finally, we emphasize the substantial limitations and challenges to facilitate further research and development. This comprehensive review might provide a directional, prompt guide for the designation and fabrication of additional innovative holey nanostructures for emerging applications.